DNA-rescuable allosteric inhibition of aptamer II ligand affinity by aptamer I element in the shortened Vibrio cholerae glycine riboswitch - Sherman, Eileen M. (J Biochem, 2014)
Glycine riboswitches contain two aptamers and turn on the expression of downstream genes in bacteria. Although full-length glycine riboswitches were shown to exhibit no glycine-binding cooperativity, the truncated glycine riboswitches were confirmed to bind two glycine molecules cooperatively. Thorough understanding of the ligand-binding cooperativity may shed light on the molecular basis of the cooperativity and help design novel intricate biosensing genetic circuits for application in synthetic biology. A previously proposed sequential model does not readily provide explanation for published data showing a deleterious mutation in the first aptamer inhibiting the glycine binding of the second one. Using the glycine riboswitch from Vibrio cholerae as a model system, we have identified a region in the first aptamer that modulates the second aptamer function especially in the shortened glycine riboswitch. Importantly, this modulation can be rescued by the addition of a complementary oligodeoxynucleotide, demonstrating the feasibility of developing this system into novel genetic circuits that sense both glycine and a DNA signal.